(untitled) (Research, Society and Development, 2021)
Objectives: To understand the stress faced by intensive care nurses in the face of the new coronavirus pandemic, identifying stressors and highlighting the repercussions of stress on nurses’ lives, as well as ways of coping. This is the Integrative Literature Review (RIL), a method that makes it possible to gather data obtained from previous research on aspects of the same theme. The selection of articles took into account the following inclusion criteria: articles that were available in full, in Portuguese and English , containing the presence of evidence on the theme chosen in relation to the nurses’ coping strategies for stress in the face of stress caused by the new coronavirus. Scientific articles published in the LILACS and BDENF database in the period from 2019 to 2021 that analyzed the selected descriptors were analyzed, totaling 17 scientific articles analyzed. Three categories were generated to discuss the data, namely: Stress factors found by nurses in the face of the new coronavirus pandemic; Stress repercussions on nurses’ quality of life and Individual and managerial coping strategies for occupational stress arising from the new coronavirus. Conclusions: Among the stress factors caused by the Coronavirus most cited by the studies are the exhaustive workload, the scarcity of personal protective equipment (PPE), changes in routine. The strategies mentioned were individual actions, improvements in crisis management, psychological assistance to health professionals, family support and interventions carried out in the virtual environment, such as group meetings and lectures aimed at mental strengthening.